Self-Activated SiO2/C Nanocomposite from Silica-Rich Marine Mucilage for Supercapacitor Applications - Tatli, Neriman Sinan; Yilmaz, Mete; Yilmaz, Ece Unur (Iop Publishing Ltd, 2023)
Bioresources are continually being explored as potential precursors for sustainable supercapacitor electrode materials. In this work, diatom-rich marine mucilage (MM) collected from the Marmara Sea, Turkey was used as a biomass source and converted to SiO2/Carbon nanocomposite (SiO 2 /C) through pyrolysis and acid etching. Diatom frustules acted as a highly porous silica source while algal organic matter delivered the carbonaceous part of the composite. The natural salts found in marine mucilage served as a self-activating agent and avoided the use of corrosive chemicals for the development of pores. The SiO 2 /C exhibited a competitive capacitance of 210 F g-1 at a current rate of 0.5 A g-1 in 1 M sodium sulfate (Na2SO4) aqueous electrolyte solution. The porous and durable silica skeleton improved capacitance by expanding the electrode/electrolyte interface, and the interconnected hierarchical pores ensured high electrochemical stability during long-term cycling. The mucilage-derived nanocomposite retained 80% and 70% of its capacitance after 4000 and 10,000 charge-discharge cycles, respectively. This work presents a potential solution for the management of marine mucilage by converting it into a high-value electrode material.
Keywords: biomass; marine mucilage; self-activation; nanocomposite; supercapacitor